0
44

# NCERT/CBSE MATHS Class 10 Ex-5.2 Q No.1 Solutions : Fill in the blanks in the following table, given that a is the first term, d the common difference and an the nth term of the A.P.

Hy Friends Welcome On NCERT MATHS SOLUTIONS !! Today we are going to solve the Question : Fill in the blanks in the following table, given that a is the first term, d the common difference and an the nth term of the A.P.of Exercise 5.2 Question No 1 Solutions (Arithmetic Progressions) of Class 10th, which will prove to be very helpful for you.

# CBSE/NCERT MATHS Class 10 Ex-5.2 Q No. 1 Solutions

If you are a student of CBSE, today we are going to give you the CBSE / NCERT Chapter : Arithmetic Progressions Exercise 5.2 Question No – 1 Solutions . Hope you like this post about Class 10th Maths Solution.

Here we would like to tell you that there are other websites on which the students demanded the Solution of NCERT MATHS Chapters, we had promised them that we will soon send you the questions of Class 9, And we completed our promise to them.We asked the good knowledgeable teachers of mathematics and asked them to solve the issues of CBSE’s mathematical questions and also said that the answers to our questions are such that the students have no difficulty in solving all those questions.

### Arithmetic Progressions CHAPTER : 5

n this progression, for a given series, the terms used are the first term, the common difference between the two terms and nth term.

Suppose, a1, a2, a3, ……………., an is an AP, then; the common difference “ d ” can be obtained as; In this progression, for a given series, the terms used are the first term, the common difference between the two terms and nth term.

a, a + d, a + 2d, a + 3d, a + 4d, ………. ,a + (n – 1) d

### (i) a = 7, d = 3, n = 8, an = ?

We know that,
For an A.P. an = a + (n − 1) d
= 7 + (8 − 1) 3
= 7 + (7) 3
= 7 + 21 = 28
Hence, an = 28

### (ii) a = −18, n = 10, an = 0, d = ?

We know that,
an = a + (n − 1) d
0 = − 18 + (10 − 1) d
18 = 9d
d = 18/9 = 2
Hence, common difference, = 2

### (iii) Given thatd = −3, n = 18, an = −5

We know that,
an = a + (n − 1) d
−5 = a + (18 − 1) (−3)
−5 = a + (17) (−3)
−5 = − 51
a = 51 − 5 = 46
Hence, a = 46

### (iv) a = −18.9, d = 2.5, an = 3.6, n = ?

We know that,
an = a + (n − 1) d
3.6 = − 18.9 + (n − 1) 2.5
3.6 + 18.9 = (n − 1) 2.5
22.5 = (n − 1) 2.5
(n – 1) = 22.5/2.5
n – 1 = 9
n = 10
Hence, n = 10

### (v) a = 3.5, d = 0, n = 105, an = ?

We know that,
an = a + (n − 1) d
an = 3.5 + (105 − 1) 0
an = 3.5 + 104 × 0
an = 3.5
Hence, an = 3.5